Nietzsche's 'will to power' and its Egotistic Character: Focus on Santayana's Critique of Nietzsche - Muhammad Ateeq (National University of Modern Languages (NUML), Islamabad, 2022)
Nietzsche's idea of 'will to power' is one of the most influential concepts of history of philosophy that emerges out as a result of his criticism of certain knowledge and tradition morality. The rejection of certain knowledge and traditional morality lead Nietzsche to regard human interest and 'supremacy' as most prior. Nietzsche conceives 'will to power' as act of 'free spirit'. He believes that 'will to power' being act of 'free spirit' is an inner potential by virtue of which men overcome their false beliefs which are barriers in human projection and authenticity of self. Santayana argues that 'will to power' is a mistaken concept. He believes that 'life' is not necessarily assertion of power to get supremacy over others. He raises an objection that the idea of 'will to power' ultimately leads to admiration of 'egotism' that takes superiority of human for granted and creates disharmony between human and reality. Santayana links Nietzsche's thought to German philosophical tradition that pursues 'free spirit' and authenticity of self but embraces egotism. For Santayana, one can pursue authenticity of self through his wisdom and creativeness like Greek who had been supporter of 'free spirit' but always had harmony with reality. This paper aims to explore Santayana's question that inquires how authenticity of self can be achieved without egotistic implication. I will revisit the notion of authenticity of self by giving an analysis of Nietzsche's theory of 'will to power' and Santayana's critique of this theory.